The National Competency-Based Teacher Standards (NCBTS) Among the Students of the College of Education (Asia Pacific Journal of Social Innovation, 2024)
This study describes and compares the National Competency-Based Teacher Standards (NCBTS) level of competence between the graduating and graduates of the College of Education on the basis of the standards set by CHED per CMO #30, s2004 and CMO #52, s2007. Questionnaires were answered by twenty six (26) graduating and forty four (44) graduates; and by all administrators of CED and administrators of private and public schools that hired CED graduates. Results showed that both the graduating and graduates had acquired high level of competences as assessed by the student respondents themselves, teachers, and administrators. Based on NCBTS standards, the graduates demonstrated better performance than thegraduating students probably because they had been hired already as teachers and have applied the theories they have learned in their pre-service education.